Backbone-modified oligonucleotides containing a butanediol-1,3 moiety as a 'vicarious segment' for the deoxyribosyl moiety--synthesis and enzyme studies. - Wilk, A (1990)
Sequential single replacement of nucleosides within the decanucleotide d[GGGAATTCCC] (7) by means of a butanediol-1,3 residue allowed us to obtain a set of ten decanucleotides containing 'vicarious' (V) carbon-phosphate fragments. These analogues were further used as substrates for svPDE, nuclease PI and EcoR1 endonuclease. Interestingly, replacement of any of the nucleosides within the canonical sequence ...GAATTC... by the butanediol-1,3 'vicarious' segment discriminates such constructs 8c-h as substrates for Eco-R1 enzyme.